Overweight in patients with chronic obstructive pulmonary disease needs more attention: a cross-sectional study in general practice. (December 2017) - Verberne, Lisa; Leemrijse, Chantal; Swinkels, Ilse; van Dijk, Christel; de Bakker, Dinny; Nielen, Mark
Abstract Guidelines for management of chronic obstructive pulmonary disease (COPD) primarily focus on the prevention of weight loss, while overweight and obesity are highly prevalent in patients with milder stages of COPD. This cross-sectional study examines the association of overweight and obesity with the prevalence of comorbid disorders and prescribed medication for obstructive airway disease, in patients with mild to moderate COPD. Data were used from electronic health records of 380 Dutch general practices in 2014. In total, we identified 4938 patients with mild or moderate COPD based on spirometry data, and a recorded body mass index (BMI) of ≥21 kg/m2 . Outcomes in overweight (BMI ≥ 25 and <30 kg/m2 ) and obese (BMI ≥30 kg/m2 ) patients with COPD were compared to those with a normal weight (BMI ≥ 21 and <25 kg/m2 ), by logistic multilevel analyses. Compared to COPD patients with a normal weight, positive associations were found for diabetes, osteoarthritis, and hypertension, for both overweight (OR: 1.4–1.7) and obese (OR: 2.4–3.8) patients, and for heart failure in obese patients (OR: 2.3). Osteoporosis was less prevalent in overweight (OR: 0.7) and obese (OR: 0.5) patients, and anxiety disorders in obese patients (OR: 0.5). No associations were found for coronary heart disease, stroke, sleep disturbance, depression, and pneumonia. Furthermore, obese patients were in general more often prescribed medication for obstructive airway disease compared to patients with a normal weight. The findings of this study underline the need to increase awareness in general practitioners for excess weight in patients with mild to moderate COPD. Chronic lung disease: Watching weight in the early stages Doctors should pay more attention to weight management in patients with mild chronic lung disease, say researchers in the Netherlands. While guidelines for treating chronic obstructive pulmonary disease (COPD) focus primarily on preventing weight-loss in severe COPD, around 65 per cent of patients with mild COPD are overweight or obese. Excessive weight exacerbates symptoms and triggers co-morbidities, and so can impact heavily on COPD healthcare provision. Lisa Verberne and co-workers at the Netherlands Institute for Health Services Research analyzed data from 315 Dutch general practices in 2014, identifying 3404 patients were classified as overweight or obese and 1534 as normal weight. So in total 4938 patients were identified. The team compared this cohort with COPD patients of normal weight, and found they were at higher risk of diabetes, osteoarthritis and hypertension. Obese patients were also at risk of heart failure and were prescribed more medication for COPD.